Synthesis, characterisation, cytotoxicity and antibacterial studies of green synthesised silver nanoparticles using leaves of Polyalthia sclerophylla - Mudhafar, Mustafa; Alsailawi, H. A.; Zainol, Ismail; Jaafar, Che Nor Aiza (Universiti Putra Malaysia, 2022)
The study was initiated to prepare silver nanoparticles (AgNPs) by using the green method with the objective to examine the biomedical properties of AgNPs from cytotoxicity and antibacterial properties against MG-63 human cell line and Staphylococcus Aureus (S. aureus) as Gram-positive and Escherichia Coli (E. coli), respectively. The rapid green method was performed by using silver nitrate (AgNO3) and crude extract of leaves of Polyalthia sclerophylla (CEPS) as the initiator and reducer, respectively. Two different concentrations of AgNO3 were used to prepare two AgNPs sizes; the prepared samples were labelled as AgNPs-a and AgNPs-b respectively. AgNPs-a and AgNPs-b were determined for their chemical, physical and biomedical properties by using various characterisation techniques including Energy Dispersive X-Ray Analysis (EDX) and ultraviolet-visible spectroscopy (Uv-vis). Other techniques included Scanning Transmission Electron Microscopy (STEM) and Scanning Electron Microscopy (SEM). The results showed that the wavelength of AgNPs-a was 436 nm, while the AgNPs-b showed 441 nm. Prepared samples were shown spherical in their shapes according to SEM and STEM images. The size of the particles was not the same, whereas, the diameter size range of AgNPs-a was from 48nm to 68 nm, while the AgNPs-b showed a range from 59 nm to 77 nm. Prepared samples showed availability for the MG-63 cells of more than 83 % for all concentrations after 24 hours. It was found that AgNPs had more inhibition for the bacteria growth against both of the bacteria. The study had demonstrated that non-toxic prepared samples have the ability to use as an antibacterial agent, with nano sizes that can be used safely in the medical and biological fields.